2018
DOI: 10.1002/aoc.4467
|View full text |Cite
|
Sign up to set email alerts
|

DFT/TDDFT insight into the impact of ring size of the NHC chelating unit of high effective phosphorescent Platinum (II) complexes

Abstract: Uncovering the photodeactivation mechanisms of unique N‐heterocyclic carbene (NHC)‐based transition metal complexes is favorable for designing more high‐efficiency phosphorescent materials. In this work, four bidentate platinum (II) complexes with NHC‐chelate are investigated by the density functional theory (DFT) and time‐dependent density functional theory (TDDFT) to probe into how the ring size of NHC‐chelate unit influences on electronic structures and the phosphorescent properties. To illustrate the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The five‐membered heterocycles containing atoms N and O coordinating with metals are also frequently reported. For example, Yan X et al reported the impact of ring size of the NHC chelating unit of high effective phosphorescent Platinum (II) complexes, among which the designed complex Pt‐4 with five‐membered NHC‐ring can serve as a highly efficient phosphorescent material in the future . Wu N et al synthesized and characterized three cyclometalated iridium (III) complexes containing monodentate five‐membered heterocyclic ligands and demonstrated that these complexes can act as novel dual‐mode light‐mediated anticancer agents …”
Section: Introductionmentioning
confidence: 99%
“…The five‐membered heterocycles containing atoms N and O coordinating with metals are also frequently reported. For example, Yan X et al reported the impact of ring size of the NHC chelating unit of high effective phosphorescent Platinum (II) complexes, among which the designed complex Pt‐4 with five‐membered NHC‐ring can serve as a highly efficient phosphorescent material in the future . Wu N et al synthesized and characterized three cyclometalated iridium (III) complexes containing monodentate five‐membered heterocyclic ligands and demonstrated that these complexes can act as novel dual‐mode light‐mediated anticancer agents …”
Section: Introductionmentioning
confidence: 99%
“…The popular meta-GGA M06-L functional [20][21][22][23] was selected to study the entire reaction mechanism because the coupling of benzoic acid and phenyl alkynyl ether, the initial process of this reaction system, was catalyzed by Ag + . The highly parameterized M06-2X functional [24][25][26][27][28] was also employed to describe the coupling of the following coupling reaction of the generated α-acyloxy enol ester and dihydroisoquinoline without transition metals, and was compared with the M06-L results. Both the M06-L [29][30][31] and M06-2X [32,33] functionals can obtain reliable relative energies in describing noncovalent interactions.…”
mentioning
confidence: 99%